Intraoperative Endoscopic Retrograde Cholangiographies at Pasteur Hospital: A review of morbidity and mortality from 2016 to 2021 - Gabito, Isabel; Charquero, Pablo; González, Rosana; González Calcagno, Fernando; Piazze Pages, Álvaro (Cirugía del Uruguay, 2025)
Introduction: Management of common bile duct stones (CBD) involves multiple options. Techniques like laparoendoscopic rendezvous have improved clinical outcomes, reduced complications, and healthcare costs. This study examines the morbidity and mortality of intraoperative Endoscopic Retrograde cholangiopancreatography (ERCP) during laparoscopic cholecystectomies. Materials and Methods: A retrospective study was conducted assessing patients undergoing intraoperative ERCP plus laparoscopic cholecystectomy over a 6- year period. Data such as indication for procedure, findings, extraction methods, admission/discharge dates, complications and mortality were recorded. Results: Between 2016 and 2021, 468 ERCP procedures were performed, with 46 being intraoperative. Standard common bile duct cannulation was most common, with a smaller percentage being true rendezvous procedures. The therapeutic success rate was high, with a low complication rate. No complications like post-ERCP pancreatitis were recorded. Selective common bile duct cannulation via rendezvous is associated to lower rates of post-ERCP pancreatitis. There was no mortality in the series. Conclusions: The combined procedure of intraoperative ERCP plus laparoscopic cholecystectomy is effective and safe, resolving both pathologies in a single intervention. With a high success rate and low morbidity, its main limitation lies in the need for available resources and coordination with specialized endoscopic teams in advance.